Participatory Management of Territorial Communities’ Local Security: EU Experience and Practices - Dankevych Vitalii Ye.; Prokopchuk Oksana A.; Usiuk Tetiana V. (Problemi Ekonomiki, 2020)
The article purpose aims at studying the results of and prospects for further implementing the European participatory model of local security management of territorial communities amidst the local government reform in Ukraine. The research results show that it is worth implementing the European participatory model of governing united territorial communities as a means of forming their local security, activating and accumulating their adaptability. The author of the article understands the local security of territorial communities term as a state guaranteeing protection to the population’s vital interests, resistance to internal and external threats, ability to operate sustainably and progressively. Under the conditions of decentralization, the key factor for its formation is the community’s endogenous potential, which proves the feasibility of using the participatory approach as a tool for activating and accumulating adaptability. Some participatory management tools are already being used successfully at the local level and have confirmed their effectiveness. The analysis of the unite territorial communities (UTCs) in the Zhytomyr region made by the amount of income of the joint purse per 1 inhabitant in 2019 allowed to single out 3 groups of UTCs according to their income. Arguments have been suggested that further active application of the European participation experience (online questionnaires and discussions of initiatives, implementation of comprehensive programs to cover the activities of communities, etc.) will help increase the local security of communities. The scientific results received serve as the methodological basis for substantiating the proposals to increase the UTCs’ local security by intensifying the implementation of the European experience in participatory management.